HOLISTIC MORAL EDUCATION: STRENGTHENING GENERATION Z'S CHARACTER AMID DIGITAL DISRUPTION - Hamdani; Muhammad Rizki Asrul; Feti Fahmimroah; Husna; Aulia Nur Azizah; Syifa'a (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This research explores the implementation of a holistic approach to moral education, focusing on the distinct challenges Generation Z encounters in developing moral character within the dominant presence of digital media. Using a literature review with descriptive analysis, this research explores various educational resources to identify key factors in implementing holistic education for moral development. The results show that a balanced approach, which integrates cognitive skills and emotional intelligence, effectively cultivates an ethical and empathetic mindset among students. Holistic practices, such as Community Service Learning, role-playing, and mindfulness, enhance students' social responsibility, empathy, and critical thinking skills. This research highlights practical implications for educators and policymakers by identifying several challenges in implementing this approach, including resource allocation, teacher training, and cultural adaptability in diverse educational contexts. These findings underscore the need for systematic support from academic institutions and policymakers to make holistic moral education more effective. This study concludes with recommendations for further research on the long-term impact of holistic moral education on character development across various cultural backgrounds, emphasizing its role in creating an empathetic and socially responsible generation.